A school-based parenting program for children with attention-deficit/hyperactivity disorder: Impact on paternal caregivers. (June 2021) - Fabiano, Gregory A.; Schatz, Nicole K.; Lupas, Kellina; Gordon, Chanelle; Hayes, Timothy; Tower, Devon; Soto, Tamara Santos; Macphee, Fiona; Pelham, William E.; Hulme, Karen
Abstract: Engaging male caregivers within school settings is a major need within the educational field. Paternal engagement may be particularly important for children with attention-deficit/hyperactivity disorder (ADHD). Children with ADHD have increased risk for a number of poor educational outcomes, which may be attenuated by the benefits of positive male caregiver involvement. The Coaching Our Acting Out Children: Heightening Essential Skills (COACHES) program has been illustrated to be an effective approach for engaging, retaining, and improving the parenting of male caregivers of children with ADHD in clinical settings. The present study reports on the efficacy of the COACHES in Schools program, an adaptation intended for deployment in elementary school settings. Sixty-one male caregivers were randomly assigned to COACHES in Schools or a waitlist control. Results indicated that male caregivers in COACHES in Schools used significantly more praise and less negative talk in a parent-child activity relative to male caregivers in the waitlist control at post-treatment and one-month follow-up. Distal outcomes related to child behavior at home and at school were not significantly different. Implications of the results for future studies and continued efforts to engage male caregivers within school settings are discussed.